(untitled) (Quaderni di Gargnano, 2022)
This essay considers the possibilities of working through affect studies and history of emotions approaches to read Dante’s presentation of Beatrice’s death in the Vita nova, focusing on Li occhi dolenti and other material immediately following the announcement of the death of Dante’s beloved. The contribution assesses Dante’s construction of a community of the vulnerable through his careful reworking of lyric precedents, including the earlier chapters of his own text. Concentrandosi in particolare su Li occhi dolenti e su altro materiale della Vita nova immediatamente successivo all’annuncio della morte di Beatrice, il saggio esplora le possibilità di leggere la presentazione dell’evento luttuoso da parte di Dante alla luce degli studi sugli affetti e della storia delle emozioni. Il contributo mette in luce come il poeta costruisca una comunità di "vulnerabili" attraverso l’attenta rielaborazione dei precedenti lirici, compresi i capitoli precedenti del suo stesso testo.